Designing a Tailored Shoe: Enabling Customization through a Computer-Aided Design (CAD) System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The shoe industry is a very competitive industry and in order to capture the market, customized shoes are desired nowadays to satisfy consumers’ needs on style, fit and comfort. Companies need to either develop a system for quick design changes, creation of huge virtual design variations and in some cases adoption of mass-customization principles to reduce cost. Shoe-last is the “heart” of shoe making since it mainly determines the shoe shape, fashion, fit and comfort qualities. The concept of mass customization has become one of the key issues in the operations management theory and practice. Customers require an elevated variety of product choice while maintaining the sales price favorable. Therefore, manufacturers need to develop technologies and systems to deliver goods and services that meet individual customers’ needs with low or even no price premiums charged. This is only possible if the manufacturing processes are organized with near mass production efficiency. This paper investigates the application of mass customization in the footwear industry and outlines the development and implementation of this concept. This study proposed a system to enable shoe- last design changes, exploration and eventually enable mass-customization. The system enables continuous change of styling and fashion to reflect personal taste without the need for physical design.